Assessing the Effectiveness of Human Resource Management in Creating Organisational Competitiveness in a South African State-Owned Enterprise - Dlamini, Bongani Innocent; Zogli, Luther-King Junior; Muzanenhamo, Arvid (Richtmann Publishing, 2021)
South African state-owned enterprises (SOEs) have been underperforming for the past decade riddled with poor service delivery, employee retrenchments, lack of employee motivation and inability to embrace innovative approaches in management of business. There has been a call from the South African government for SOEs to self-renew and become effective in service delivery. As a result the role of human resource management (HRM) assist organisations to become effective through the use of innovative human resource practices. This paper is an investigation carried out at a selected South African SOE to determine the effectiveness of HRM in creating organisational competitiveness. A qualitative research approach was adopted where interviews were used to gather data from the company’s human resource practitioners and departmental heads. Non-probability sampling was used and 24 participants were purposively selected. The study revealed that HR practitioners do not participate in policy reviews whereas their skills are underutilised, they lack latest technology and it was noted that there is excessive control from high authorities. Received: 11 February 2021 / Accepted: 16 March 2021 / Published: 17 May 2021